Speaking Skill’s Language Anxiety Experienced by Freshers of English Language Education Department - Rosalin Ismayoeng Gusdian; Siti Nurhidayah (Universitas Islam Negeri Mataram, Indonesia, 2020)
The aims of this study is to find out the language anxiety levels encountered by the freshmen of English Language Education Department, the reasons of the language anxiety, and how the students cope with the language anxiety. It is a mixed-method study conducted in an Islamic private university in Malang. The population included 128 English Language Education Department freshmen in the academic year 2019/2020. Through convenience sampling, 32 students from six speaking classes were obtained. A survey using Foreign Language Classroom Anxiety (FLCAS) questionnaire and interview were applied as the techniques to gather the data. The findings revealed that 91% freshmen are identified to experience a medium level of anxiety (76-119). Besides, the reasons of the language anxiety included communication apprehension, fear of negative evaluation, and fear of making mistakes in the test. Several ways to cope with the language anxiety comprised practicing before class and keeping the up with the positive mind. Tujuan dari penelitian ini adalah untuk mengetahui tingkat kecemasan berbahasa yang dialami oleh mahasiswa baru Jurusan Pendidikan Bahasa Inggris, alasan kecemasan berbahasa, dan cara mahasiswa mengatasi kecemasan tersebut. Penelitian ini menggunakan metode campuran yang dilakukan di sebuah universitas swasta Islam di Malang. Populasi penelitian ini adalah 128 mahasiswa baru Jurusan Pendidikan Bahasa Inggris tahun ajaran 2019/2020. Melalui convenience sampling, diperoleh 32 siswa dari enam kelas berbicara. Teknik pengumpulan data menggunakan kuesioner Foreign Language Classroom Anxiety (FLCAS) dan wawancara. Temuan tersebut mengungkapkan bahwa 91% mahasiswa baru diidentifikasi mengalami tingkat kecemasan sedang (76-119). Selain itu, alasan kecemasan bahasa termasuk ketakutan komunikasi, takut evaluasi negatif, dan takut membuat kesalahan dalam ujian. Beberapa cara untuk mengatasi kecemasan bahasa terdiri dari berlatih sebelum kelas dan menjaga pikiran positif.